2022
DOI: 10.1093/beheco/arac091
|View full text |Cite
|
Sign up to set email alerts
|

Unlike a virgin: a meta-analytical review of female mating status in studies of female mate choice

Abstract: Studies of female mate choice commonly use virgin females as test subjects, either to control for the effects of mating or because virgin females are presumed to be more responsive to mating cues. Theory predicts that virgin females will be less choosy because they risk dying without mating. Moreover, in many species, females spend more of their lives mated than as virgins. Thus, the exclusive use of virgin females in studies of female mate choice may underestimate the strength or direction of female choice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 336 publications
2
12
0
Order By: Relevance
“…Yet, it is important to note that our results are concordant with a recent meta-analysis showing no evidence that mating status is an important factor for preference. Specifically, across species, virgin females are as choosy as mated females across reproductive isolation, inbreeding avoidance, and sexually transmitted disease scenarios (Richardson & Zuk, 2022). Our study here presents a similar finding, as males with no previous mating experience (naïve males) presented similar preferences to males with mating experience (experienced males).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it is important to note that our results are concordant with a recent meta-analysis showing no evidence that mating status is an important factor for preference. Specifically, across species, virgin females are as choosy as mated females across reproductive isolation, inbreeding avoidance, and sexually transmitted disease scenarios (Richardson & Zuk, 2022). Our study here presents a similar finding, as males with no previous mating experience (naïve males) presented similar preferences to males with mating experience (experienced males).…”
Section: Discussionmentioning
confidence: 99%
“…However, two recent meta‐analyses found no evidence that virgin and mated females differ in their choosiness (Dougherty, 2023; Richardson & Zuk, 2022) suggesting an asymmetry in the effects of female mating status on male and female mate choice. Crucially, Richardson and Zuk (2022) found that the majority of studies of female mate choice use virgin females which, combined with the results of this study, suggests that male preferences for virgin females could be influencing our broader understanding of mate choice. Our meta‐analysis suggests males generally prefer virgin females but to understand the consequences for sexual selection, we must examine how preferring virgins affects lifetime reproductive success in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…If males direct greater mating effort towards virgin females, those females may respond differently. This is especially important given that studies of female mate choice commonly only test preferences in virgin females (Richardson & Zuk, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To address this, we used standard binary choice tests (Figure 2) and multiple populations of each species to account for within-species variability. Furthermore, we used unmated (virgin) and previously mated females in P. mexicana to elucidate the potential role of previous (or absence of) mating experience (Richardson and Zuk 2023). For this particular situation we predicted stronger preferences in females that had been together with conspecific males, because individual experience might reinforce their preference and the mated females had been together only with conspecifics.…”
Section: Introductionmentioning
confidence: 99%